Local Air‐Sea Interactions at Ocean Mesoscale and Submesoscale in a Western Boundary Current. Issue 7 (30th March 2022) - Strobach, Ehud; Klein, Patrice; Molod, Andrea; Fahad, Abdullah A.; Trayanov, Atanas; Menemenlis, Dimitris; Torres, Hector
Abstract: We present results from a new, global, high‐resolution (∼3‐km for ocean and ∼6‐km for atmosphere) realistic earth system simulation. This simulation allows us to examine aspects of small‐scale air‐sea interaction beyond what previous studies have reported. Our study focuses on recurring intermittent wind events in the Gulf Stream region. These events induce local air‐sea heat fluxes above Sea Surface Temperature (SST) anomalies with horizontal scales smaller than 500‐km. In particular, strong latent heat bursts above warm SST anomalies are observed during these wind events. We show that such wind events are associated with a secondary circulation that acts to fuel the latent heat bursts by transferring dry air and momentum down to the surface. The intensity of this secondary circulation is related to the strength of small‐scale SST fronts that border SST anomalies. The study of such phenomena requires high‐resolution in both the atmospheric and oceanic components of the model. Plain Language Summary: We explore the atmospheric circulation above Sea Surface Temperature (SST) anomalies of less than 500 km‐scale using a new, global, coupled ocean‐atmosphere simulation performed at high horizontal resolution and integrated for 3 months. Our study focuses on intermittent wind events in the Gulf Stream region and the resulting local air‐sea heat fluxes above warm SST anomalies: A strong latent heat burst above these SST anomalies is observed during the intermittent wind events. Furthermore, during these events, a secondary circulation develops up to altitudes of 2, 000 m above warm SST anomalies, which results in sinking of warm and dry air and air momentum from upper levels down to the sea‐surface. Such secondary circulation is triggered by the strong wind stress divergences that develop above small‐scale SST fronts bordering the SST anomalies. The consequence is an increase of latent heat fluxes above SST anomalies. Key Points: Strong turbulent flux discontinuities observed at ocean fronts suggest the importance of small scales for air‐sea interactions Intermittent large‐scale winds together with mesoscale Sea Surface Temperature variations trigger secondary circulations in the atmospheric boundary layer Air‐sea interactions are explored under a wider range of periods and wind speeds than previously examined